Endometrial expression of FOX proteins (FOXA1 and FOXA2) in women of reproductive age with different endometrial thickness: prospective cohort comparative study - Natalia V. Aganezova; Sergey S. Aganezov; Ksenia E. Gogichashvili; Anna S. Artemyeva; Anna O. Nyuganen (IP Berlin A.V., 2023)
Aim. To evaluate the expression of FOX proteins (FOXA1 and FOXA2) in the endometrium during the implantation window in women with a history of reproductive dysfunctions with different thickness of the endometrium. Materials and methods. The prospective cohort comparative study was conducted. The main group included patients with "thin" endometrium (7 mm according to ultrasound on preovulatory days; n=52), the comparison group consisted of women with normal endometrial thickness (7 mm according to ultrasound; n=62; women of both groups with reproductive dysfunctions of unknown reason), the control group included 16 healthy fertile women. Aspiration biopsy of the endometrium was performed on the 68 days after ovulation, as well as venipuncture to obtain a sample of peripheral blood to determine the levels of sex steroids (estradiol E2 and progesterone P). A combined histological and immunohistochemical study of endometrial biopsies was performed. Results. All women had ovulatory values of progesterone P16.1 nmol/l (68 days after ovulation) and normoestrogenemia (E2, pmol/l) in the blood. E2/P was similar in all groups (p0, 05). A pronounced expression of FOXA1 was noted in women with thin endometrium significantly more often (p0.05) with various hormone-receptor characteristics of the endometrium (42% n=22 out of 52) compared with healthy participants (0%; n=0). Reduced FOXA2 expression in the uterine mucosa was significantly more often detected on 68 days after ovulation in women with "thin" endometrium (56% n=29 of 52) than in women with normal endometrial thickness, both in women from the comparison group and in healthy women from the control group (p0.05). In a generalized analysis of the expression of FOX proteins in the endometrium on days 68 after ovulation, it was generally found that every second (50%; n=57 out of 114) women with a history of reproductive disorders (with a reduced and normal M-echo value) expression of proteomic markers differed from healthy women. In the case of "thin" endometrium, more than two thirds of patients (71%; n=37 out of 52) showed differences in endometrial expression of FOX proteins compared with women without a burdened reproductive history. Conclusion. In the majority of women (71%) with a thin endometrium and a history of reproductive dysfunctions, the expression of FOX proteins in the endometrium differed from the control group. Overall, endometrial expression of FOX proteins, which is likely to be different from healthy women, in patients with reproductive dysfunctions of unknown origin is a significant predictor of reproductive failure. At the same time, such an isolated indicator as M-echo value 7 mm according to ultrasound data is not an absolute prognostic marker of endometrial receptivity disorders.